MAPA CLIMÁTICO COMO FERRAMENTA DE GESTÃO URBANA: ESTUDO NA CIDADE DE JOÃO PESSOA/PB - Souza, Vladimir; Katzschner, Lutz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The proposal of this work is to present the German methodology for the production of urban climate maps used as a tool to support decision making in city management, taking as an example a study developed in the city of João Pessoa. The methodology is based on analyzes of climatic and physical-territorial aspects that characterize the climate of urban environments according to the consideration of the energy balance of the city, determined by its thermal load (thermal energy retention capacity) and by its dynamic potential (capacity of interfering with the local wind flow). In this way, the classification and valorization of areas of the city were carried out according to a probable favor of the elevation of the air temperature and the obstruction of the wind flows (roughness). These assessments were based on the scientific knowledge of climatic behavior of climatopes, which are areas of the city with climatically homogeneous characteristics and defined by the characteristics of buildings, topography, vegetation, water bodies and open spaces. A Geographic Information System (GIS) was used for the storage, processing and presentation of the geographic information studied.